Electronification Financial Transactions for Business Operator: Legal Protection for Consumers Experienced Rejection in Cash Transaction - Yusuf Argiansyah, Hikmal; Imran Nasution, Ali (Law Development Journal, 2025)
The National Non-Cash Movement (GNNT) by Bank Indonesia has brought changes in the implementation of transaction methods that prioritize digital transaction. Therefore, some business operator on payment methods that only accept non-cash transactions (cashless-only) in their business. However, it is actually caused problems in society, especially people who prefer cash transaction methods and people who do not have access to digital payments. Research conducted using the juridical-normative method uses the statue approach and case approach in conducting research. Research shows that the implementation of payment transaction methods that only accept digital payments (cashless-only) has the potential to violate consumer rights in terms of equal and non-discriminatory treatment of consumers, especially consumers who do not have access to digital payments. Rejection of the rupiah has also been prohibited through the Currency Law and the prohibition was reaffirmed by the Deputy Governor of Bank Indonesia. Consumers who feel that their rights have been violated by cashless-only transaction methods can take legal action in the form of a lawsuit through the general court, resolving the problem through non-litigation (conciliation, mediation, or arbitration) either individually or through the Consumer Dispute Resolution Agency (BPSK), and/or can report it to the National Consumer Protection Agency (BPKN).